WRKY9 transcription factor regulates cytochrome P450 genes CYP94B3 and CYP86B1, leading to increased root suberin and salt tolerance in Arabidopsis - Krishnamurthy, Pannaga (WILEY, 2023)
10.1111/ppl.13371